Marketing Strategy on Hasanah Saving Products at KSPPS Berkah Mitra Hasanah Semarang - Nurudin Nurudin (Universitas Islam Negeri (UIN) Walisongo Semarang, 2021)
AbstractPurpose - This study aims to find out what a hasanah savings product is and the marketing strategy implemented by KSPPS Berkah Mitra Hasanah Semarang.Method - This research is a type of field research conducted at KSPPS Berkah Mitra Hasanah Genuk Semarang to explore relevant data or primary and secondary data sources. The author collects data by interview, observation, and documentation. The collected data is then analyzed by analytical descriptive method.Result - The marketing strategy carried out by KSPPS Berkah Mitra Hasanah is advertising by KSPPS Berkah Mitra Hasanah in the form of brochures, internet, MMT and souvenirs. In addition to advertising, there is also personal selling, in practice marketing KSPPS Berkah Mitra Hasanah serves and influences, offers, and directly disseminates its products to partners. There is also publicity carried out by KSPPS Berkah Mitra Hasanah through tausiyah activities at the school foundation which is a mandatory activity once a month in the last week of the month accompanied by door prizes.Implication - This research can be used as a reference in marketing KSPPS Berkah Mitra Hasanah hasanah savings products.Originality- The marketing strategy used in marketing KSPPS Berkah Mitra Hasanah hasanah savings products in Semarang is through advertising in the form of brochures, internet, MMT and souvenirs, besides that there are tausiyah activities and door prizes.